PERSEBARAN DAN POLA KEPADATAN MOLUSKA DIHUTAN BAKAU - Arie Budiman (Research Center for Biology-Indonesian Institute of Sciences, 2009)
Mangrove molluscs data collected from some mangrove forest in Indonesia (Sumatra, Kalimantan, Java, Mollucas, and Papua) are used in order to understand the mangrove molluscs distribution and pattern of species abundance. The results of the present study strongly suggest three models (or combination of them) of distribution, i.e. (1) molluscs (especially bivalve) only recruit into certain microhabitat, in wich they reach larger densities; (2) certain species of mollusc may recruit widely, but suffer increase mortality in certain microhabitats; and (3) molluscs(especialy for mobile animals, such as many gastropods) may actively move among macrohabitats, increasing local densities in some of those.The correlation between features of habitat and abundance of molluscs which can be described as preference are discussed.